Proteus mirabilis outcompetes Klebsiella pneumoniae in artificial urine medium through secretion of ammonia and other volatile compounds - Juarez, Guillermo Esteban (2020)
Klebsiella pneumoniae and Proteus mirabilis form mixed biofilms in catheter-associated urinary tract infections. However, co-inoculation of P. mirabilis with K. pneumoniae in artificial urine medium (AUM) resulted in a drastic reduction of K. pneumoniae cells in both biofilm and planktonic growth. Here, the mechanism behind this competitive interaction was studied. Both pH and aqueous ammonia (NH3aq) increased in mixed cultures (to 9.3 and 150 mM, respectively), while K. pneumoniae viable cells dramatically diminished over time (>6-log reduction, p < 0.05). Mixed cultures developed in either 2-(N-morpholino) ethanesulfonic acid (MES)-buffered AUM (pH 6.5) or AUM without urea did not show bacterial competition, evidencing that the increase in pH and/or NH3aq concentration play a role in the competitive interaction. Viability of K. pneumoniae single-species cultures decreased 1.5-log in alkaline AUM containing 150 mM NH3aq after 24 h inoculation, suggesting that ammonia is involved in this inter-species competition. Besides NH3aq, additional antimicrobials should be present to get the whole competitive effect. Supernatants from P. mirabilis-containing cultures significantly diminished K. pneumoniae viability in planktonic cultures and affected biofilm biomass (p < 0.05). When subjected to evaporation, these supernatants lost their antimicrobial activity suggesting the volatile nature of the antimicrobial compounds. Exposure of K. pneumoniae to volatile compounds released by P. mirabilis significantly decreased cell viability in both planktonic and biofilm cultures (p < 0.05). The current investigation also evidenced a similar bactericidal effect of P. mirabilis volatiles over Escherichia coli and Morganella morganii. Altogether, these results evidence the secretion of ammonia and other volatile compounds by P. mirabilis, with antimicrobial activity against gram-negative uropathogens including K. pneumoniae. This investigation provides novel insight into competitive inter-species interactions that are mediated by production of volatile molecules.